Professional development of heritage language teachers : the example of Lithuanian heritage language school in Iceland - Jurgita Motiejunaite 1974- (2019)
The aim of this paper is to explore literature related to teachers’ professional development in heritage language schools as units of non-formal education with a special focus on Lithuanian heritage language school in Iceland. Due to the limited opportunities of education and professional development the place of teachers of community-based heritage language schools among the teaching professions is not clear, though it is agreed that it differs from the teachers of formal educational settings. The need for heritage language education is widely recognized in most of the Western countries. Nevertheless, the implementation is often politicized, slow, challenging and highly dependent on state and local governments. The investigation of the situation in Canada and some European Nordic countries shows positive development. Research on heritage language schools often is focused on teacher or student experiences or through ethnographic observation of the heritage language community schools. Lithuanian heritage language teaching is researched as a part of Lithuanian identity development or through structural description of school settings. However, heritage language teachers’ professional development is little researched both in Iceland and abroad. The documentation and sharing of the information related to the quality of teaching, teacher professionalism and professional development could be improved in all heritage language schools of Lithuanian immigrant communities in different countries, including Lithuanian heritage language school in Iceland.